Optimal Ordering Strategies for Announced Price Increases - Taylor, Sam G.; Bradley, Charles E. (Operations Research, 1985)
The familiar model for determining the optimal ordering strategy, given an announced price increase, assumes that the buyer has an opportunity to place an order at the end of the next economic order quantity cycle before the price increase takes effect. This paper extends the price increase model by relaxing the requirement on the timing of the price increase. Specifically, we develop optimal ordering strategies for situations where the price increase becomes effective at any future specified time. We also calculate savings for alternate ordering strategies.